Urbanization may limit impacts of an invasive predator on native mammal diversity. Issue 4 (26th January 2017) - Reichert, Brian E.; Sovie, Adia R.; Udell, Brad J.; Hart, Kristen M.; Borkhataria, Rena R.; Bonneau, Mathieu; Reed, Robert; McCleery, Robert
Abstract: Aim: Our understanding of the effects of invasive species on faunal diversity is limited in part because invasions often occur in modified landscapes where other drivers of community diversity can exacerbate or reduce the net impacts of an invader. Furthermore, rigorous assessments of the effects of invasive species on native communities that account for variation in sampling, species‐specific detection and occurrence of rare species are lacking. Invasive Burmese pythons ( Python molurus bivittatus ) may be causing declines in medium‐ to large‐sized mammals throughout the Greater Everglades Ecosystem (GEE); however, other factors such as urbanization, habitat changes and drastic alteration in water flow may also be influential in structuring mammal communities. The aim of this study was to gain an understanding of how mammal communities simultaneously facing invasive predators and intensively human‐altered landscapes are influenced by these drivers and their interactions. Location: Florida, USA. Methods: We used data from trail cameras and scat searches with a hierarchical community model that accounts for undetected species to determine the relative influence of introduced Burmese pythons, urbanization, local hydrology, habitat types and interactive effects between pythons and urbanization on mammal species occurrence, site‐level species richness, and turnover. Results: Python density had significant negative effects on all species except coyotes. Despite these negative effects, occurrence of some generalist species increased significantly near urban areas. At the community level, pythons had the greatest impact on species richness, while turnover was greatest along the urbanization gradient where communities were increasingly similar as distance to urbanization decreased. Main conclusions: We found evidence for an antagonistic interaction between pythons and urbanization where the impacts of pythons were reduced near urban development. Python‐induced changes to mammal communities may be mediated near urban development, but elsewhere in the GEE, pythons are likely causing a fundamental restructuring of the food web, declines in ecosystem function, and creating complex and unpredictable cascading effects.